2019
DOI: 10.1111/bjh.16064
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of synchronous systemic and central nervous system (CNS) involvement of diffuse large B‐cell lymphoma are dictated by the CNS disease: a collaborative study of the Australasian Lymphoma Alliance

Abstract: Summary De novo diffuse large B‐cell lymphoma (DLBCL) presenting with synchronous central nervous system (CNS) and systemic disease (synDLBCL) is not well described and is excluded from clinical trials. We performed a retrospective analysis of 80 synDLBCL patients treated across 10 Australian and UK centres. Of these patients, 96% had extranodal systemic disease. CNS‐directed treatment with combination intravenous cytarabine and high‐dose methotrexate (“CNS‐intensive”) (n = 38) was associated with favourable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…For the 50 patients with DLBCL or HGBCL with synchronous CNS and systemic involvement at diagnosis, the 2-year PFS of 43% and OS of 57% reported in our study are in line with outcomes reported in similar retrospective studies showing 2-3-year PFS and OS of 42-45% and 44-56%, respectively. 37,[39][40][41] Improved outcomes have been reported with the use of more intensive first-line chemotherapy options, with or without consolidative autologous stem cell transplantation, in non-randomized clinical trials that included small numbers of patients with DLBCL or HGBCL with synchronous CNS and systemic involvement at diagnosis. 10,42 In addition to its single-center retrospective nature, our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For the 50 patients with DLBCL or HGBCL with synchronous CNS and systemic involvement at diagnosis, the 2-year PFS of 43% and OS of 57% reported in our study are in line with outcomes reported in similar retrospective studies showing 2-3-year PFS and OS of 42-45% and 44-56%, respectively. 37,[39][40][41] Improved outcomes have been reported with the use of more intensive first-line chemotherapy options, with or without consolidative autologous stem cell transplantation, in non-randomized clinical trials that included small numbers of patients with DLBCL or HGBCL with synchronous CNS and systemic involvement at diagnosis. 10,42 In addition to its single-center retrospective nature, our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Data on optimal treatment for patients with secondary CNS involvement at initial presentation are even scarcer [10, 21, 22]. Available retrospective analysis underlines the role of intensive CNS-directed chemotherapy for controlling CNS manifestation of lymphoma in these patients [23, 24]. However, the value of consolidating ASCT in this patient cohort is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of consolidating ASCT in this patient cohort is not well defined. Damaj et al [23] retrospectively reported a significant survival benefit for patients receiving a consolidative ASCT (19 of 60 patients receiving ASCT with a 3-year overall survival of 75% compared to 29%), whereas Wight et al [24] could not observe a significant difference for consolidative ASCT in patients treated with intensive CNS-directed therapy when matched for induction outcomes (38 of 80 patients receiving intensive CNS induction therapy, of which 14 received ASCT with a nonsignificant 2-year overall survival of 66% compared to 56%).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study of genes and signal pathways regulated during tumorigenesis will contribute to the study of the pathological mechanism of DLBC and guide the therapeutic effect [ 2 , 3 ]. It usually occurs only outside the central nervous system or is less isolated from the central nervous system [ 4 ]. It is very aggressive and progresses rapidly, so early treatment is the critical way to save the lives of DLBC patients.…”
Section: Introductionmentioning
confidence: 99%